2007
DOI: 10.1021/cg060701t
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of Triglyceride Monolayers on Water and Mica Surfaces

Abstract: ABSTRACT:The structure and the stability of tripalmitin (PPP), tristearin (SSS), and triarachidin (AAA) monolayers at the air-water interface are investigated with the Langmuir method. The Langmuir-Blodgett (LB) layers obtained by deposition on mica were investigated with atomic force microscopy (AFM). Our experiments show that the three triglycerides can form monolayers with molecules in trident conformation at the air-water interface. We determined the equilibrium spreading pressure π eq below which such mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 19 publications
5
17
0
Order By: Relevance
“…Like in monocomponent systems [22,23] we found higher domains on top of the PPP-SSS monolayer. Most of them had a thickness of 3.570.1 nm (Figs.…”
Section: Article In Presssupporting
confidence: 72%
See 4 more Smart Citations
“…Like in monocomponent systems [22,23] we found higher domains on top of the PPP-SSS monolayer. Most of them had a thickness of 3.570.1 nm (Figs.…”
Section: Article In Presssupporting
confidence: 72%
“…In this mode we chose barrier velocities of the order of 1 cm/min, which according to the literature should be slow enough that the Langmuir film stays close to thermodynamic equilibrium. It should be mentioned however, that in previous work [23] we have shown that, for condensed phases this compression rate is still too high for the film to be in equilibrium.…”
Section: Langmuir Methodsmentioning
confidence: 70%
See 3 more Smart Citations